An in-line spectrophotometer on a centrifugal microfluidic platform for real-time protein determination and calibration. Issue 18 (17th August 2016) - Ding, Zhaoxiong; Zhang, Dongying; Wang, Guanghui; Tang, Minghui; Dong, Yumin; Zhang, Yixin; Ho, Ho-pui; Zhang, Xuping
Abstract : We demonstrated an inline spectrophotometer on centrifugal microfluidics based on the PEDD method, and used it for real-time protein determination and calibration on a chip. Abstract : In this paper, an in-line, low-cost, miniature and portable spectrophotometric detection system is presented and used for fast protein determination and calibration in centrifugal microfluidics. Our portable detection system is configured with paired emitter and detector diodes (PEDD), where the light beam between both LEDs is collimated with enhanced system tolerance. It is the first time that a physical model of PEDD is clearly presented, which could be modelled as a photosensitive RC oscillator. A portable centrifugal microfluidic system that contains a wireless port in real-time communication with a smartphone has been built to show that PEDD is an effective strategy for conducting rapid protein bioassays with detection performance comparable to that of a UV-vis spectrophotometer. The choice of centrifugal microfluidics offers the unique benefits of highly parallel fluidic actuation at high accuracy while there is no need for a pump, as inertial forces are present within the entire spinning disc and accurately controlled by varying the spinning speed. As a demonstration experiment, we have conducted the Bradford assay for bovine serum albumin (BSA) concentration calibration from 0 to 2 mg mL −1 . Moreover, a novel centrifugal disc with a spiral microchannel is proposed for automatic distribution and metering of the sample to all the parallel reactions at one time. The reported lab-on-a-disc scheme with PEDD detection may offer a solution for high-throughput assays, such as protein density calibration, drug screening and drug solubility measurement that require the handling of a large number of reactions in parallel.